Left atrial strain — a current clinical perspective - Karolina Kupczyńska; Giulia Elena Mandoli; Matteo Cameli; Jarosław D. Kasprzak (2021)
The speckle-tracking technique has become an easily accessible, quick-to-use, and straightforward tool for assessing advanced myocardial function. Achievements in the analysis of the left atrium have demonstrated that it plays an important role in the physiology and pathophysiology of the circulatory system. Deformation analysis allows the detection of even subtle functional abnormalities when atrial enlargement is not yet detected. Thus, left atrial strain has a documented diagnostic and prognostic value in many clinical scenarios. Furthermore, this technique is increasingly entering routine clinical practice. The analysis becomes possible thanks to new tools that simplify the speckle-tracking assessment. Left atrial strain improves diagnostic possibilities of standard echocardiographic examination, and its diagnostic and prognostic value is sometimes comparable with more advanced and less available techniques. In this review, we discuss the principles of performing strain analysis and the results of current research, and thus the potential possibilities of sophisticated atrial assessment application in various clinical scenarios.